PENGARUH MICRO-INFLUENCER VS VIRTUAL INFLUENCER (AI): ANALISIS PERBANDINGAN TINGKAT KEPERCAYAAN DAN LOYALITAS KONSUMEN MILENIAL DI KOTA BANJARMASIN - Sucidha, Irma; Yuliani, Yuliani (JURNAL LENTERA BISNIS, 2026)
This study aims to analyze and compare the impact of micro-influencers and virtual influencers on consumer trust and loyalty among the millennial generation in Banjarmasin. Amidst the digital marketing transformation, the effectiveness of human figures versus AI-based characters remains a significant subject of debate. Utilizing a quantitative, causal-comparative research design, this study surveyed 125 respondents to evaluate how these two influencer categories shape consumer behavior. Multiple linear regression analysis reveals that micro-influencers exert a more dominant and significant influence on both consumer trust (0.452) and loyalty (0.385) compared to virtual influencers (0.214 and 0.152, respectively). These findings underscore that the "human" element, emotional connection, and perceived authenticity offered by micro-influencers are crucial for millennials. Nevertheless, virtual influencers remain relevant for their aesthetic appeal, innovation, and consistency. The study concludes that these influencer types are complementary rather than replacements, and their utility depends on campaign objectives and audience characteristics.